The state of information in 2021: news about documentation, libraries, internet, digital content and scientific communication - Baiget, Tomí s (Anuario ThinkEPI, 2022)
Compilation of the main Spanish and world events and news produced during 2021 about documentation, libraries, internet, digital content and scientific communication. The notes have been identified and/or written by professionals and academics belonging mostly to the scientific and editorial boards of the Anuario ThinkEPI yearbook and the Profesional de la información journal.
Keywords: News; Ephemeris; Anniversaries; Information; Documentation; Libraries; Databases; Journals; Books; Indicators; Information sources